Keterdedahan Media Massa dan Perubahan Sosiokultural Komunitas Pesantren - Saleh, Amiruddin (Departement of Communication and Community Development Sciences, Faculty of Human Ecology, 2009)
Pesantren [traditional Islamic boarding school] is a typical traditional religious education institution that has been presence in Indonesia since centuries. In maintaining its cultural-survival, pesantren is facing dramatic challenge due to rapid development of communications and information as brought in by modern technology. The massive influx of messages coming from mass media is really distorting the traditional codes of cultures as maintained in the pesantren education system. This phenomenon has brought about dramatic socio-cultural changes in the pesantren as a social entity. To see how deep is the influence of mass media exposure bringing about social change in pesantren, a study has been carried out. The aim of the study is to know the interplaying relationship between personal characteristics of the pesantren community members with mass media exposure and socio-cultural changes. The study revealed that personal characteristics and social economic background of students of pesantren have generally a very strong and significant correlation to the mass media exposure. The study concludes that significant influence of mass media exposure on the students has resulted in significant socio-cultural changes in the pesantren.